2002
DOI: 10.1590/s1516-635x2002000100007
|View full text |Cite
|
Sign up to set email alerts
|

Efeito dos Níveis de Cantaxantina na Dieta Sobre o Desempenho e Qualidade dos Ovos de Poedeiras Comerciais

Abstract: O experimento teve como objetivo estudar os efeitos de níveis de cantaxantina sobre o desempenho e a coloração das gemas dos ovos de galinhas poedeiras. Foram utilizadas 384 galinhas da linhagem Hisex Brown, em um delineamento em blocos ao acaso, contendo seis tratamentos (0, 12, 24, 36, 48 e 60 ppm de cantaxantina), com oito repetições de oito aves por parcela. O período experimental foi de 56 dias. A coleta de ovos foi realizada diariamente e a análise de coloração dos ovos foi efetuada com o abanico colorim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
4
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 1 publication
2
17
4
16
Order By: Relevance
“…Egg production was also affected at the same proportion as feed intake as propolis dietary levels increased. This result differs from that found by Garcia et al (2002) when analyzing the addition of canthaxanthin in layer diets. Galal et al (2008) and Khojasteh & Shivazad (2006) found that high concentrations of propolis in the diet improved performance.…”
Section: Layer Performancecontrasting
confidence: 99%
See 2 more Smart Citations
“…Egg production was also affected at the same proportion as feed intake as propolis dietary levels increased. This result differs from that found by Garcia et al (2002) when analyzing the addition of canthaxanthin in layer diets. Galal et al (2008) and Khojasteh & Shivazad (2006) found that high concentrations of propolis in the diet improved performance.…”
Section: Layer Performancecontrasting
confidence: 99%
“…On the other hand, redness (a*) value was higher in the yolks of T1 hens (control) relative to the other treatments, while yellowness (b*) values were lower in yolk of eggs laid by hens fed 3% propolis in the diet. The present results differ from those found by Garcia et al (2002) who observed a direct correlation between the increase egg yolk color intensity as the product addition level increased. The effect of propolis in the hens' diet was reduced by the decrease in a* and b* values and by the increase in L* values.…”
Section: Egg Qualitycontrasting
confidence: 99%
See 1 more Smart Citation
“…A redução na pigmentação da gema foi 22 e 48% (p < 0,05), para os níveis baixo e alto de sorgo, respectivamente, quando comparado com a dieta controle (Tabela 3). Reduções proporcionais na pigmentação da gema, com a substituição de milho por sorgo, também foram verificadas em outros autores (Zanzad et al, 2000;Garcia et al, 2002), sendo que esses efeitos são devido ao baixo teor de xantofilas (Subramanian e Metta, 2000). A suplementação de páprica, em ambos os níveis, aumentou a pigmentação da gema, superando a dieta controle.…”
Section: Resultados E Discussão Resultados E Discussão Resultados E Dunclassified
“…Casca (%) A literatura (Silva et al, 2000;Garcia et al, 2002) tem mostrado que o uso de pigmentos naturais nas rações à base de sorgo não influencia no desempenho das poedeiras.…”
Section: Egg Weightunclassified